Risk Factors for Shoulder Stiffness: Current Concepts - Cucchi, Davide; Marmotti, Antongiulio; De Giorgi, Silvana; Costa, Alberto; D'Apolito, Rocco; Conca, Marco; Russo, Alessandro; Saccomanno, Maristella F.; de Girolamo, Laura; SIGASCOT Research Committee (Joints, 2017)
Shoulder stiffness is a condition of painful restriction of the glenohumeral range of motion. Numerous risk factors for primary and postoperative shoulder stiffness have been described. This article summarizes the known aspects of the pathophysiology of shoulder stiffness, with special attention to elements of molecular biology and genetics, which could influence the risk of developing shoulder stiffness. Furthermore, the role of hormonal and metabolic factors, medical disorders, drugs, and of other published risk factors for primary and postoperative shoulder stiffness is reviewed and discussed. Finally, aspects related to shoulder surgery and postoperative rehabilitation protocols, which could influence the development of postoperative stiffness are presented.
Keywords: shoulder stiffness; frozen shoulder; adhesive capsulitis; shoulder arthroscopy; inflammation